Pelatihan Pemanfaatan Articial Intelegence pada Dosen Fakultas Ilmu Komputer Universitas Duta Bangsa Surakarta dalam Pengelolaan Pembelajaran Efektif - Nurohman Nurohman; Saryadi Saryadi (Universitas Kristen Indonesia Toraja, 2024)
The application of artificial intelligence in education has brought significant changes in learning methods and classroom management. This paper discusses the Application of AI for Learning training held for lecturers at UDB Surakarta with the aim of improving understanding and skills in the application of AI technology. The training method includes a combination of theoretical and practical sessions. The theory session ran in several stages, namely a discussion on the introduction of AI, demonstrations of AI tools and technologies such as ChatGPT, Copilot, and Gemini. Practices of using AI in the creation of learning materials, assessment of learning outcomes, and writing scientific articles. The training, which was attended by 12 lecturers, provided hands-on experience in the application of AI in the world of education. The results of the training showed a significant improvement in the understanding and skills of the participants, with 91.67% of participants feeling satisfied and hoping for similar training on a regular basis. The training evaluation includes an analysis of participant feedback that shows that the training is helpful in preparing for learning, creating teaching modules, and other learning tools. The evaluation of the training results leads to the conclusion that this training is effective in improving lecturers' competence in using AI, encouraging creativity in learning, and is expected to increase effectiveness in learning.